The Impacts of the Alteration in Agriculture on the Environment and Ecosystem in Sarawak, Malaysia - Tanaka, Sota; Mohd Effendi, Bin Wasli; Joseph Jawa, Kendawang; Sakurai, Katsutoshi (Graduate School of Kuroshio Science, Kochi University, 2014)
In Sarawak, Malaysia, while large scale oil palm plantations have been rapidly expanding, shifting cultivation has been altering toward more intensified systems or reducing in its area or activities. Some local farmers prefer planting commercial crops such as rubber, pepper and oil palm rather than their traditional crop of upland rice. Issues relating to the influence of shifting cultivation and oil palm plantation on the environment and ecosystem are still disputable because the discussion is usually based on the stereotypical views lacking ecological evidence. In this keynote report for the 7th International Symposium on Kuroshio Science, several topics are presented related to the impacts of shifting cultivation and oil palm plantations on the environment and ecosystem in Sarawak, Malaysia, based on previous studies. We emphasize that further field research is needed with collaboration between multi-disciplinary international researchers to provide empirical data in order to reach conclusions and resolve the issues.